Characteristics and Risk Factors of Diabetic Retinopathy Patients in West Java, Indonesia - Setiawan, Grace; Rini, Mayang; Ratnaningsih, Nina; Memed, Feti Karfiati; Dahlan, Muhammad Rinaldi (Majalah Kedokteran Bandung, 2024)
Diabetic retinopathy (DR) is the major microvascular complication of diabetes mellitus (DM) and responsible as the leading cause of vision loss among working-age adults. With the estimated DM cases reaching 578 million in 2030, public health systems are faced with challenges of increasing costs of implementation and maintenance of DR screening program in people with DM. This study aimed to describe characteristics and risk factors of DR among patients of a Primary Health Care Center in West Java, Indonesia. This was a cross-sectional study during the period of March 2021 until June 2022 on 1,080 participants. Among these participants with DM, 28.89% (25.16–33.12% [95% CI]) were classified to have DR. A total of 32.69% (28.14–36.71 [95% CI]) participants with DR had vision threatening DR (VTDR). The prevalence of DR in this study was higher in women (77.23%) with a mean age of 57.26 ± 9.17 and duration of DM of ≥5-years (56.01%), blood glucose level <200 mg/dL (63.79%), high systolic blood pressure (52.03%), high diastolic blood pressure (39.07%), normal BMI (55.5%), high waist circumference (43.7%), and high HbA1C (3.42%). A total of 1,041 (96.39%) participants were using antidiabetic drugs, and 9.63% of them were currently smoking. This study showed that diastolic blood pressure, abnormal abdominal circumference, and high HbA1C levels were more prevalent in DR and VTDR groups. The findings of this study represent the current characteristics of DR patients in West Java and can be used as a baseline or comparison data for other regions in Indonesia.